PROFILING KIMIA SAMPEL KOKAIN SITAAN DI BALI DENGAN KROMATOGRAFI LAPIS TIPIS – SPEKTROFOTODENSITOMETRI - Wirasuta, I Made Agus Gelgel; Hidayatullah, Kusuma; Sahara, Emmy; Tavip, Roedy Aris (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
The seized cocaine samples by Narcotic Police in Denpasar have been carried out profiling. Cocaine’s were eluted on Al-TLC Si GF 254 and spot scanned on Spectrophotodensitometric-method. Eight seized cocaine’s were presented relative peaks pattern, with chromatograms similarity of 99.81%.  Based on the similarity, all of cocaine’s, could be classified into one group or same origin.
Keywords: drugs profiling, cocaine, TLC, Spectrophotodesitometric